Effects of andiroba (Carapa guianensis) oil in ticks: ultrastructural analysis of the synganglion of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) - Roma, Gislaine Cristina [UNESP]; Camargo-Mathias, Maria Izabel [UNESP]; Nunes, Pablo Henrique [UNESP]; Remedio, Rafael Neodini [UNESP]; Faria, Adriano Uemura de [UNESP]; Bechara, Gervasio Henrique [UNESP] (Elsevier B.V., 2015)
The present study performed an analysis of the ultrastructural changes induced by andiroba seed oil in the synganglion of Rhipicephalus sanguineus female ticks, aiming to provide scientific grounds to help in the creation of more specific and efficient methods of control. The synganglion consists of a mass of fused nerves externally covered by the neural lamella, a uniform and acellular layer. Just below, the perineurium is found, formed by glial cells. Internally, the synganglion is subdivided into an outer cortical region (cortex), which contains the cellular bodies of the neural cells and an inner region, the neuropile, formed by a set of nerve fibers (extensions of the neural cells). The results showed that the synganglion of females exposed to andiroba oil showed structural changes, such as: irregular and apparently thinner neural lamella, perineurium glial cells presenting large cytoplasmic vacuoles, decrease in the extensions of glial cells, separation of cortex cells, which were formerly attached through their membranes, neural cells presenting irregular plasma membranes and cytoplasm with autophagic vacuoles and mitochondria with disorganized cristae and in process of degeneration. This study confirmed the neurotoxic action of the andiroba oil, which would probably be able to impair the neural functions. Thus, it is suggested that this product has the potential to be used as an alternative method to control ticks.
Keywords: Central nervous system; Vegetable oil; Semi-engorged females; Neurotoxic action